Kearifan Lokal dan Aktifitas Filantropi Perantau Sulit Air Sepakat (SAS) dalam Menghadapi Revolusi Industri 4.0 - Addiarrahman Addiarrahman (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
This article describes the practice of philanthropy of the diaspora of Sulit Air Sepakat (SAS) in facing the industrial revolution 4.0. Merantau as a form of local wisdom of the Minangkabau people based on Adat Bersendi Syara’, Syara’ Bersendi Kitabullah (ABS-SBK), forming Islamic philanthropic behavior that can keep up with the times. However, the management system applied is still traditional. After SAS was officially incorporated as a Perkumpulan, it was a strategic change in knitting the power of diaspora philanthropy. Through participatory action research, this article reveals the philanthropic activities of Sulit Air diasporas in the era of industrial revolution 4.0 is to establish SAS information systems, utilization of social media, and programs to improve the quality of human resources.